(3GdGbJUGO GdOhdj (B:s (3GdfXQjI hGdJWHjbGJ (B/s - (3Cejf, gLjQ YOfGf Rcjs ((3YeGf(B: s (3OGQ CKQGA(B, s, 2010)
-(3fXQjI GdJLGQI GdOhdjI hJhSjYgG,GbJUGOjGJ GdSjGSI GdJLGQjI,GbJUGOjGJ GdfbO GdOhdjs
(3eUGOQ GdcJGH U(B.305s
Keywords: (3GdGbJUGO GdOhdjs; (3GdEbJUGO GdOhdj(B- (3fXQjGJs; (3GdJLGQI GdNGQLjIs